2004
DOI: 10.5558/tfc80694-6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of understory white spruce response to release from overstory aspen

Abstract: Meta-analysis was used to summarize the research results on the growth response of understory white spruce to release from overstory aspen from different studies available from published and unpublished sources. The data were screened for the suitability for meta-analysis. Treatment effect sizes were calculated using response ratio from mean cumulative increments of released and control trees since release in height, diameter, and volume and modeled using a polynomial mixed effect regression procedure. Predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…However, by year 14 this difference was no longer statistically significant. Consistent with the 5th-year observations in this study and the results of other studies (Brand, 1991;Groot, 1999;Wagner et al, 1999;Man and Greenway, 2004), diameter growth, relative to height, has a lower priority in growth allocation and is more sensitive to changes in light availability (Lanner, 1985). In this study RCD at year 14 was more responsive than height to harvest intensity, especially for jack pine.…”
Section: Survival and Growth Of Planted Treessupporting
confidence: 94%
See 1 more Smart Citation
“…However, by year 14 this difference was no longer statistically significant. Consistent with the 5th-year observations in this study and the results of other studies (Brand, 1991;Groot, 1999;Wagner et al, 1999;Man and Greenway, 2004), diameter growth, relative to height, has a lower priority in growth allocation and is more sensitive to changes in light availability (Lanner, 1985). In this study RCD at year 14 was more responsive than height to harvest intensity, especially for jack pine.…”
Section: Survival and Growth Of Planted Treessupporting
confidence: 94%
“…The height of natural conifer regeneration present on the study site at year 14 suggests that most of these young conifers (largely balsam fir) existed prior to the harvesting treatments. Their growth benefited from the release effect of the canopy removal (Man and Greenway, 2004). The results from Pré vost and Pothier (2003) in Quebec and Man et al (2008) in Ontario suggested that a partially harvested canopy supports conifer recruitment than uncut and clearcut treatments.…”
Section: Natural Regenerationmentioning
confidence: 94%
“…As reported in the literature (Man and Greenway 2004), the data presented in this paper demonstrated that diameter increment was the most responsive with a rise of 152%. Height increment increased 76% over the control and total annual volume increment was elevated by 83%.…”
Section: Impact On Growthsupporting
confidence: 66%
“…After aspen overstory removal, white spruce releases regardless of age; however, several reports indicate that trees aged 20 to 60 years are most responsive (Steneker 1963, Lees 1966, Yang 1989. Notably accelerated growth rates have been reported after release, with diameter growth usually responding more significantly than height growth, and total annual volume increment increasing up to 93% as compared to the unharvested control (Lees 1966;Yang 1989Yang , 1991Man and Greenway 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These management approaches, however, largely focus on maximizing conifer production through the control of competing vegetation, which in the boreal often involves hardwood shrubs or trees (Pitt et al 2010). In addition to the many ecological benefits such as enhanced structural and biological diversity, habitat availability and resistance to pests (Kelty 1992(Kelty , 2006, mixedwood conditions may also result in greater overall productivity (Man and Greenway 2004, Lieffers et al 2007, Cortini et al 2012. While this previous work suggests the potential for a beneficial interaction between tree species in boreal mixedwoods, the mechanisms whereby these interactions influence growth at the individual tree level remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%